La primera nevada de Clifford - Bridwell, Norman; Mlawer, Teresa (New York : Scholastic, 1998)
When Clifford, the big red dog, is feeling sad, Emily Elizabeth and her friends do everything they can think of to cheer him up.
"Mariposa, Scholastic en Espaol"--Cover.
Keywords: Dogs -- Fiction; Snow -- Fiction; Spanish language materials